Confronting the"Imposter Syndrome" in the Adult Learning Classroom - Lorenzo Bowman; Glenn A Palmer (Adult Education Research Conference, 2017)
This paper examines the experiences of two African American male professor in confronting the "Imposter Syndrome." The relevant literature on the Imposter Syndrome is used to analyze the experiences of these two educators and strategies are advanced for addressing the phenomenon of both a personal and a professional level.
Keywords: Adult Leaning; Imposter Syndrome